Estudio y diseño geometrico de las calles de la ciudadela las palmeras de norte a sur en la calles Napo, Zamora Chinchipe, los Rios y Loja, y de Este a Oeste en la calles Luis Espinoza, calle, Calle G, y Calle H, con aproximadamente 4,66 Km. en la ciudad de Santa Rosa, Cantón Santa Rosa, Provincia de el Oro - Lanchi Estrada, Robert Ivan (2015)
The following project ah done to develop the knowledge acquired throughout our years of studies and in turn in order to meet the different needs in the population optimizing a better quality of life and hoping this will be a source of information or guide for future projects to be implemented. When performing a terrestrial communication 1st order it leads to improve not only the economy but the quality of life of the inhabitants of the area where the project is realized.